Impact of varying wave periods of COVID‐19 on in‐hospital mortality and length of stay for admission through emergency department: A territory‐wide observational cohort study. Issue 2 (13th October 2021) - Xiong, Xi; Wai, Abraham K. C.; Wong, Janet Y. H.; Tang, Eric H. M.; Chu, Owen C. K.; Wong, Carlos K. H.; Rainer, Timothy H.
Abstract: Background: The COVID‐19 pandemic has been associated with excess mortality and reduced emergency department attendance. However, the effect of varying wave periods of COVID‐19 on in‐hospital mortality and length of stay (LOS) for non‐COVID disease for non‐COVID diseases remains unexplored. Methods: We examined a territory‐wide observational cohort of 563, 680 emergency admissions between January 1 and November 30, 2020, and 709, 583 emergency admissions during the same 2019 period in Hong Kong, China. Differences in 28‐day in‐hospital mortality risk and LOS due to COVID‐19 were evaluated. Results: The cumulative incidence of 28‐day in‐hospital mortality increased overall from 2.9% in 2019 to 3.6% in 2020 (adjusted hazard ratio [aHR] = 1.22, 95% CI 1.20 to 1.25). The aHR was higher among patients with lower respiratory tract infection (aHR: 1.30 95% CI 1.26 to 1.34), airway disease (aHR: 1.35 95% CI 1.22 to 1.49), and mental disorders (aHR: 1.26 95% CI 1.15 to 1.37). Mortality risk in the first‐ and third‐wave periods was significantly greater than that in the inter‐wave period ( p ‐interaction < 0.001). The overall average LOS in the pandemic year was significantly shorter than that in 2019 (Mean difference = −0.40 days; 95% CI −0.43 to −0.36). Patients with mental disorders and cerebrovascular disease in 2020 had a 3.91‐day and 2.78‐day shorter LOS than those in 2019, respectively. Conclusions: Increased risk of in‐hospital deaths was observed overall and by all major subgroups of disease during the pandemic period. Together with significantly reduced LOS for patients with mental disorders and cerebrovascular disease, this study shows the spillover effect of the COVID‐19 pandemic.